NATIONAL RUSSIAN GUIDELINES ON APPLICATION OF THE METHODS OF HOLTER MONITORING IN CLINICAL PRACTICE - L. M. Makarov; V. N. Komolyatova; O. A. Kupriyanova; E. V. Pervova; G. V. Ryabykina; A. V. Sobolev; V. M. Tikhonenko; A. N. Turov; Y. V. Shubik; A. V. Ardashev; R. M. Baevsky; L. A. Balykova; et al. (Российский кардиологический журнал, 2014)
.